Educating Before Birth via Talking to the Baby in the Womb: Prenatal Innovations - Shelina Bhamani (Journal of Education and Educational Development, 2020)
Education is the only major weapon that enables nations to progress socio-economically and gives a huge rise to their human development index. More so, it is considered to be the most fundamental requirement for poverty eradication, for addressing socio-political issues and for stabilizing peace and harmony among nations. Education is a lifelong process and does not have a preset parameter for its accessibility and provision (Sharkey, 1998). Learning is innate and natural and the human mind is set to learn since its conception. Additionally, in the recent era, investigations are focused on education and learning even before birth and extensive emphasis is now paid on experimenting on prenatal education by providing pre-birth interventions for babies inside the womb (Hepper, 1991; Kleindorfer & Robertson, 2013; Partanen, et al., 2013; Sharkey, 1998).
Keywords: Early Child Learning; Prenatal innovations; Womb